Phosphate diabetes in patients with chronic fatigue syndrome. Issue 870 (April 1998) - De Lorenzo, F.; Hargreaves, J.; Kakkar, V. V.
Abstract : Phosphate depletion is associated with neuromuscular dysfunction due to changes in mitochondrial respiration that result in a defect of intracellular oxidative metabolism. Phosphate diabetes causes phosphate depletion due to abnormal renal re-absorption of phosphate be the proximal renal tubule. Most of the symptoms presented by patients with phosphate diabetes such as myalgia, fatigue and mild depression, are also common in patients with chronic fatigue syndrome, but this differential diagnosis has not been considered. We investigated the possible association between chronic fatigue syndrome and phosphate diabetes in 87 patients who fulfilled the criteria for chronic fatigue syndrome. Control subjects were 37 volunteers, who explicitly denied fatigue and chronic illness on a screening questionnaire. Re-absorption of phosphate by the proximal renal tubule, phosphate clearance and renal threshold phosphate concentration were the main outcome measures in both groups. Of the 87 patients with chronic fatigue syndrome, nine also fulfilled the diagnostic criteria for phosphate diabetes. In conclusion, we report a previously undefined relationship between chronic fatigue syndrome and phosphate diabetes. Phosphate diabetes should be considered in differential diagnosis with chronic fatigue syndrome; further studies are needed to investigate the incidence of phosphate diabetes in patients with chronic fatigue syndrome and the possible beneficial effect of vitamin D and oral phosphate supplements.